2001
DOI: 10.1523/jneurosci.21-23-09367.2001
|View full text |Cite
|
Sign up to set email alerts
|

Functional Interactions between Tumor and Peripheral Nerve: Changes in Excitability and Morphology of Primary Afferent Fibers in a Murine Model of Cancer Pain

Abstract: We used a murine model to investigate functional interactions between tumors and peripheral nerves that may contribute to pain associated with cancer. Implantation of fibrosarcoma cells in and around the calcaneus bone produced mechanical hyperalgesia of the ipsilateral paw. Electrophysiological recordings from primary afferent fibers in control and hyperalgesic mice with tumor revealed the development of spontaneous activity (0.2-3.4 Hz) in 34% of cutaneous C-fibers adjacent to the tumor (9-17 d after implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
67
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(76 citation statements)
references
References 52 publications
9
67
0
Order By: Relevance
“…Second, this model allows examination of the electrophysiological responses of primary afferent fibers in mice with tumor-evoked hyperalgesia. We have determined that implantation of fibrosarcoma cells results in the sensitization of a subpopulation of C-nociceptors that innervate the plantar surface of the hind paw (Cain et al, 2001). Furthermore, the peripheral terminals of primary afferent fibers innervating the skin overlying the tumor show morphological changes such as an increase in epidermal nerve fibers during the early development of tumor-evoked hyperalgesia, upregulation of purinergic P2X 3 receptors on these fibers, and subsequent decrease in epidermal innervation (Gilchrist et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, this model allows examination of the electrophysiological responses of primary afferent fibers in mice with tumor-evoked hyperalgesia. We have determined that implantation of fibrosarcoma cells results in the sensitization of a subpopulation of C-nociceptors that innervate the plantar surface of the hind paw (Cain et al, 2001). Furthermore, the peripheral terminals of primary afferent fibers innervating the skin overlying the tumor show morphological changes such as an increase in epidermal nerve fibers during the early development of tumor-evoked hyperalgesia, upregulation of purinergic P2X 3 receptors on these fibers, and subsequent decrease in epidermal innervation (Gilchrist et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study was to determine if a more potent cannabinoid, CP 55,940, attenuates tumor-evoked cutaneous mechanical hyperalgesia in a well-characterized murine model of cancer pain. In this model, implantation of osteolytic fibrosarcoma cells into and around the calcaneous bone produces robust mechanical hyperalgesia and sensitization of C nociceptors (Cain et al, 2001;Wacnik et al, 2001). This model will allow us to correlate the antihyperalgesic effects of cannabinoids to its effects on tumor-evoked sensitization of nociceptors.…”
Section: Introductionmentioning
confidence: 99%
“…Intraepidermal nerve fiber density. Intraepidermal nerve fiber (IENF) density was examined in hindpaw footpads using previously reported techniques (18). Briefly, footpads were collected from the plantar surface of the hindpaws before animal perfusion, fixed in Zamboni's fixative (2% paraformaldehyde, 0.2% picric acid, and 0.1 mol/l sodium phosphate buffer) for 14 h, and cryoprotected through a series of sucrose gradients and embedded in OCT. Free-floating 30-m footpad sections were stained with anti-PGP 9.5 antibody (a panaxonal marker) (19).…”
Section: Methodsmentioning
confidence: 99%
“…The subsequent development of thermal hyperalgesia may be secondary to release of pro-nociceptive substances by the tumor cells, such as endothelin-1, a mediator able to induce thermal hyperalgesia (34). Furthermore tumor development has been shown to induce development of spontaneous electrical activity and sensitization of C-fibers which provide innervation in and around the affected bone (35). The role of endogenous opioid-ergic analgesia systems has been also demonstrated by Mantyh's group, in another animal cancer pain model, wherein genetically modified transgenic mice under control of a promoter, spontaneously develop pancreatic cancer.…”
Section: The Mouse Bone Cancer Pain Modelmentioning
confidence: 99%
“…Release of endothelin-1 from tumor cells (34) has been implicated in the induction of thermal hyperalgesia. Furthermore, in the same model of bone cancer pain in mice, tumor growth has been reported to induce development of spontaneous electrical activity and sensitization of Cfibers, which provide innervation in and around the affected bone (35). It has been shown that some small unmyelinated primary afferent fibers express endothelin receptors, the activation of which may result in sensitization or excitation (61).…”
Section: Information Derived From the Mouse Bone Cancer Pain Modelmentioning
confidence: 99%